Pengaruh Monitoring Obat, Konseling Obat dan Identifikasi MRPs terhadap Penerapan Keselamatan Pasien - Mulisda Mardiantina (Syntax Corporation Indonesia, 2022)
Patient safety is something much more important than just service efficiency. The knowledge and skills of hospital pharmacists play an important role in the implementation of patient safety. Behavior that does not understand, forget, lack of attention, carelessness, and carelessness in maintaining patient safety will risk errors and will result in injury to patient safety. The purpose of this study was to analyze the effect of drug monitoring, drug counseling and identification of MRPs on the implementation of patient safety. This research method is cross sectional. The population in this study were all pharmacists who worked at hospital X in Tangerang. The sampling technique used purposive sampling which involved 28 pharmacists as respondents. The instrument used is a questionnaire and an observation sheet on the ability of pharmacists about patient safety. The results of the analysis showed that the p value for drug monitoring is p = 0.049, drug counseling is p = 0.018 and the identification of MRPs is p = 0.000. All p values are smaller than = 0.05 so it can be concluded that there is a positive and significant effect between drug monitoring, drug counseling and identification of MRPs on the implementation of patient safety. Suggestions from this study for hospitals to further improve the quality of nursing services related to patient safety in accordance with national patient safety guidelines.